Effective Academic Writing 1. The Paragraph - Savage A. Alice (New York, Oxford University Press, 2007)
The Effective Academic Writing series teaches the writing modes, rhetorical devices, and language points required for academic success. Each of the three levels provides user-friendly activities and self-contained lessons that make teaching and learning manageable. Each unit introduces a theme and a writing task and then guides the student writer through the process of gathering ideas, organizing an outline, drafting, revising, and editing. Students are given the opportunity to explore their opinions, discuss their ideas, and share their experiences through written communication. Effective Academic Writing 1: The Paragraph reviews sentence structure and prepares students to write academic paragraphs, while introducing five essential rhetorical modes. Features: Compelling and authentic readings inspire student interest before writing modes are introduced. Rhetorical presentations and exercises refine writing skills. Language presentations and exercises complement writing genres. Editing checklists promote peer feedback and aid students in revising their written work. Timed paragraph writing and testing material at the end of each unit reinforce skills and prepare students for in-class writing as wells high-stakes assessment. Grammar presentations and practice are correlated to Grammar Sense J.